2004
DOI: 10.1111/j.1365-2044.2004.03810.x
|View full text |Cite
|
Sign up to set email alerts
|

A homemade model for training in cricothyrotomy*

Abstract: SummaryWe describe a simple, homemade model for teaching cricothyrotomy. It can easily be constructed from materials found in every anaesthetic room and is cheap, portable and usable several times before requiring replacement. We also describe evaluation of the model in a two-part study. First, 20 anaesthetic trainees, both with and without prior experience of percutaneous cricothyrotomy ⁄ tracheotomy, cannulated the 'trachea' using two percutaneous airway sets (Ravussin jet ventilation catheter, then scored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…13 Low-cost, lowfidelity simulators have been described, but they often require considerable time to build and often require animal tissues. [18][19][20] Although the benefits of low-vs high-fidelity models are unclear, low-fidelity cricothyrotomy simulation appears to be equivalent to high-fidelity simulation for learning procedural steps, whereas operator preference for realism clearly favors animal models. 13,17,21 It is not uncommon for a trainee to have the opportunity to attempt a cricothyrotomy once or twice on a cadaver or a high-fidelity model, but it is rare that they would have multiple attempts.…”
Section: Discussionmentioning
confidence: 93%
“…13 Low-cost, lowfidelity simulators have been described, but they often require considerable time to build and often require animal tissues. [18][19][20] Although the benefits of low-vs high-fidelity models are unclear, low-fidelity cricothyrotomy simulation appears to be equivalent to high-fidelity simulation for learning procedural steps, whereas operator preference for realism clearly favors animal models. 13,17,21 It is not uncommon for a trainee to have the opportunity to attempt a cricothyrotomy once or twice on a cadaver or a high-fidelity model, but it is rare that they would have multiple attempts.…”
Section: Discussionmentioning
confidence: 93%
“…Mannequin or cadaver training reduces cricothyrotomy time and improves the success rate in anesthesiologists and residents [26,27]. Interestingly, a simple and inexpensive model for cricothyrotomy training [28] produced skill acquisition that was comparable to a vastly more expensive human patient simulator, and both these methods of cricothyrotomy training translated effectively to human cadavers [19]. Similar to the trend in U.S. anesthesiology training programs, a combined strategy of laboratory, workshop, and human patient simulator training in Canada was recently described as a model for advanced airway management education that included infraglottic techniques (eg, cricothyrotomy, retrograde wire) [29].…”
Section: Discussionmentioning
confidence: 97%
“…Common complications are injury to the thyroid, cricoid, posterior tracheal wall, anterior oesophageal wall, hemorrhage, and failure to provide an airway (7) . Mobility of the trachea is another important reason for failure.Consequently, the reported complication rate of emergency cricothyrotomy usually exceeds 40%, although one study reported a rate of %6 (2,8) .…”
Section: Discussionmentioning
confidence: 99%
“…Its indications are prolonged mechanical ventilation, acute upper airway obstruction, and increased secretions in the lower airways that cannot be aspirated (1) . A cricothyrotomy is a simpler surgical procedure that can be used to save patients' lives, even outside an operating room (2) .…”
Section: Introductionmentioning
confidence: 99%